"Every time when I make a mistake in class, educators would say, you babymama you must keep quiet:" Challenges confronting teenage mothers when re-engaging with secondary school education in a Johannesburg secondary school, South Africa. Issue 3 (2nd April 2020) - Malatji, Hlologelo; Dube, Nkosiyazi; Nkala-Dlamini, Busisiwe
ABSTRACT: In many societies, a girl child is often the one who bears the brunt of unplanned pregnancy. In some instances the pregnancy affects their education, since a decision has to be made on whether or not to continue schooling during and after the pregnancy. This study explored the challenges confronting teenage mothers when they reengaged with secondary school education post-pregnancy in Johannesburg. Qualitative interviews were used to collect data from the teen mothers. Data collected was analyzed using thematic analysis methods. Key findings indicated that some educators were hostile toward the teenage mothers, and treated them differently. This was due to the poor comprehension of applicable policies meant to protect the education interest of pregnant learners and teenage mothers in schools. Recommendations are made for the education authorities to ensure that relevant policies are followed by educators when confronted with learner pregnancy related complication.